KOMUNIKASI INTERPERSONAL ANTARA PELATIH DAN ATLET DALAM MENINGKATKAN PRESTASI DI BADMINTON PLAJOE SELECTION - Ratu Mutialela Carapeboka; Aulia Amanda; Bangkit Sanjaya (Bajang Institute, 2022)
Interpersonal communication is very important upon improving achievement athletes. One of the way for that by new coach is two way and supportive relation and that called interpersonal communication. This research aims to determine the effectiveness and resistance of coaches in conducting interpersonal communication. This research uses descriptive qualitative method with the selection of informants using purposive sampling technique that selects five selected informants. The informants in this study consisted of 1 badminton coach and 6 female badminton athletes who had undergone the badminton training process at the Badminton Plajoe Selection Association. Data processing techniques using interviews, observation and documentation. For data analysis techniques, it refers to checking the validity of the data.